Making Waves: Collaboration in the time of SARS-CoV-2 - rapid development of an international co-operation and wastewater surveillance database to support public health decision-making - Lundy, Lian; Kassinos, Despo Fatta; Slobodnik, Jaroslav; Karaolia, Popi; Cirka, Lubos; Kreuzinger, Norbert; Castiglioni, Sara; Bijlsma, Lubertus; Dulio, Valeria; Deviller, Geneviève; Lai, Foon Yin; Barneo, Manuela; et al. (Elsevier, 2021)
The presence of SARS-CoV-2 RNA in wastewater was first reported in March 2020. Over the subsequent months, the potential for wastewater surveillance to contribute to COVID-19 mitigation programmes has been the focus of intense national and international research activities, gaining the attention of policy makers and the public. As a new application of an established methodology, focused collaboration between public health practitioners and wastewater researchers is essential to developing a common understanding on how, when and where the outputs of this non-invasive community-level approach can deliver actionable outcomes for public health authorities. Within this context, the NORMAN SCORE “SARS-CoV-2 in sewage” database provides a platform for rapid, open access data sharing, validated by the uploading of 276 data sets from nine countries to-date. Through offering direct access to underpinning meta-data sets (and describing its use in data interpretation), the NORMAN SCORE database is a resource for the development of recommendations on minimum data requirements for wastewater pathogen surveillance. It is also a tool to engage public health practitioners in discussions on use of the approach, providing an opportunity to build mutual understanding of the demand and supply for data and facilitate the translation of this promising research application into public health practice.
Keywords: Wastewater surveillance; NORMAN/SCORE SARS-COV-2 in sewage (SC2S) database; SARS-CoV-2 RNA